1998
DOI: 10.1055/s-2007-1001360
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Programmed Endoscopic Follow-up Examinations on the Rebleeding Rate of Gastric or Duodenal Peptic Ulcers Treated by Injection Therapy: A Prospective, Randomized Controlled Trial

Abstract: Programmed endoscopic follow-up examinations with eventual retreatment in patients locally injected for an acute or recent hemorrhage from a gastric or duodenal ulcer did not influence their outcome when compared to patients receiving only a second endoscopic intervention upon evidence for recurrent hemorrhage. Scheduled control endoscopies cannot be recommended after an initial successful endoscopic treatment of peptic ulcer bleeding when selection of the patients for second-look endoscopy is directed by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
95
1
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(103 citation statements)
references
References 0 publications
3
95
1
4
Order By: Relevance
“…First, an extremely high proportion of active bleeders (70%) were enrolled, which makes it difficult to generalize the results to the average patient with bleeding peptic ulcer disease. Persistent high risk stigmata led to retreatment in 84% of the patients, which is a much higher proportion than in most other studies (19% to 59%) (13,16,17). Third, there was no case of early (within 24 h) rebleeding.…”
Section: Why Consider a Routine Second Look?mentioning
confidence: 61%
See 3 more Smart Citations
“…First, an extremely high proportion of active bleeders (70%) were enrolled, which makes it difficult to generalize the results to the average patient with bleeding peptic ulcer disease. Persistent high risk stigmata led to retreatment in 84% of the patients, which is a much higher proportion than in most other studies (19% to 59%) (13,16,17). Third, there was no case of early (within 24 h) rebleeding.…”
Section: Why Consider a Routine Second Look?mentioning
confidence: 61%
“…Third, there was no case of early (within 24 h) rebleeding. In most other studies, approximately 20% of patients had already experienced rebleeding before the second endoscopy at 24 h (13,16). Fourth, 40% of rebleeding episodes occurred extremely late (more than 72 h after initial endoscopy), at six and 10 days, respectively.…”
Section: Why Consider a Routine Second Look?mentioning
confidence: 88%
See 2 more Smart Citations
“…Routine "second look" endoscopy, in the absence of established rebleeding or patient instability, has gone out of vogue after studies showed no benefit with regards to clinically significant outcomes for unselected patient populations, 65 although there may be a role in high risk patients. 66,67 Repeat therapeutic endoscopy may be indicated (depending on local endoscopic and surgical expertise) if there is clinical evidence of re-bleeding or if the initial therapeutic procedure was unsuccessful or partially successful.…”
Section: "Second-look" Endoscopy and Endoscopic Re-treatmentmentioning
confidence: 99%